A closer look on Filipino ESL teachers’ best practices: A basis for a multiculturally responsive and eclectic teaching approach - Dizon Jr, Rodolfo P.; Nanquil, Luisito M. (Yayasan Mitra Persada Nusantara, 2024)
English as a Second Language teaching in the Philippines has become popular worldwide, particularly among Asian students. This is a strong indicator that Filipino teachers are able to facilitate effective teaching-learning process amidst the presence of multilingualism and multiculturalism. Banking on this premise, this paper attempted to explore on the best practices of ESL teachers employ in promoting the macro skills among their culturally diverse students. To achieve this objective, a general qualitative inquiry design using a validated structured interview guide served as the primary data collection tool. The study had 8 Filipino ESL teachers who were purposively chosen following criteria set by the researcher. Results showed that the teachers purposely differentiate their approaches depending on the levels, cultural background, learning styles, and preferences of the students. Moreover, these approaches are generally aligned with the aim of scaffolding the students to improve their English language proficiency. Some of these include role-playing, essay writing, book reports, modeling, sentence diagramming, and the like. These results are congruent with the three approaches Martin (2014) claim namely Communicative Language Teaching (CLT), English for Specific Purposes (ESP), and Task-Based Language Teaching (TBLT). From these findings, the researcher framed the significance of a multiculturally responsive and eclectic teaching approach. Multiculturalism is found to be a significant factor in the ESL classrooms as it can create an inclusive a classroom atmosphere which can promote successful acquisition and learning of the English language.